PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT REINDO - Teti Rohayati (Fakultas Ekonomi Universitas Borobudur, 2019)
This is a survey project: using a sample which was taken from the certain population. Thepopulation under study were taken from PT. ReINDO, (204) in which the sample were 111respondents, using simple random sample; the sample recruitment technique which was donerandombly and each person in the population has a possibility as a sample.Data analysis wasdone by using descriptive analytic and statistics (correlation, coefficient determinants, t-test, Ftest and regression).Based on descriptive analysis this research found that development, working motivationand employee performance were quite high.Mean while, based on statistic analysis, this researchfound that human resource development and working motivation have positive impact foremployee performance as a single factor and multiple factors.The development of human resource has a positive effeckt and significance corelation foremployee performance in PT. ReINDO with correlation ceficcient value 0,451 and coefficientdeterminant 20,3 % wich was explained by using regression : Y= 19,51+0,955 Xt. Workingmotivations has a positive effect and significance for employee performance in PT. ReINDO, withcorrelation coefficient value 0,646 and coefficient determinant wich was explained by regression: Y + 26,391+0,963X2. These positive impacts haave linier correlation which was explained thatthe higher working motivation the more increased the employee performance; and vice versa.Keyword : working motivation and employee performance were quite high, working motivationand employee performance were quite high.